2004
DOI: 10.1536/jhj.45.885
|View full text |Cite
|
Sign up to set email alerts
|

A Second Mitral Valve Replacement in a Patient With Hereditary Hemorrhagic Telangiectasia (Osler's Disease)

Abstract: SUMMARYA 62-year-old female with Osler's disease was admitted to our hospital because of fever and cardiac failure. The patient had undergone a mitral valve replacement (MVR) using a Carpentier-Edwards prosthetic valve 14 years earlier. A bacterial examination of arterial blood identified Streptococcus mitis. No arteriovenous malformations were detected in visceral organs. The patient underwent MVR using the same prosthetic xenograft after conservative treatment and management of repetitive epistaxis and decay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…Although we knew that our patient had AVMs and mucosal telangiectasia before her operation, she suffered only mild hemorrhage perioperatively. Her recurrent epistaxis resolved after the operation, as described in our previous case report [ 7 ]. Several measures were taken during the preoperative and postoperative periods to prevent life-threatening hemorrhage, including the administration of estrogen before the operation, not inserting a nasogastric tube, and discontinuance of anticoagulant drugs pre- and postoperatively [ 8 , 9 ].…”
Section: Discussionsupporting
confidence: 63%
“…Although we knew that our patient had AVMs and mucosal telangiectasia before her operation, she suffered only mild hemorrhage perioperatively. Her recurrent epistaxis resolved after the operation, as described in our previous case report [ 7 ]. Several measures were taken during the preoperative and postoperative periods to prevent life-threatening hemorrhage, including the administration of estrogen before the operation, not inserting a nasogastric tube, and discontinuance of anticoagulant drugs pre- and postoperatively [ 8 , 9 ].…”
Section: Discussionsupporting
confidence: 63%
“…Despite the high risk of developing severe bacterial infections, infective endocarditis associated with HHT is relatively rare. To our knowledge, there are only eight cases of infective endocarditis in patients with HHT [ 9 16 ]. Among them, only two cases were treated medically without valvular surgery (Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] To our knowledge, our patient is the first with HHT to undergo the Bentall operation following aortic valve replacement. Although a mechanical valve was selected in the first replacement operation, we used a tissue valve in the second, taking into consideration repetitive epistaxis and gastric bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Ishikawa, et al also reported the replacement of mitral valve with a tissue valve in a patient with HHT. 5) Benzadón, et al 3) recommend maintaining the activated clotting time >400s, which prevents bleeding by decreasing the activity of the coagulation system during surgery.…”
Section: Discussionmentioning
confidence: 99%